2004
DOI: 10.1177/153857440403800206
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Associated with Renal Insufficiency and Endovascular Repair of Abdominal Aortic Aneurysms: A 5-Year Experience

Abstract: To evaluate the outcome of patients with renal insufficiency undergoing endovascular repair of abdominal aortic aneurysm (AAA), data were prospectively collected between 1998 and 2003 on patients undergoing elective repair of their AAA with a stent graft. The patients were divided into 2 groups: those with serum creatinine (Crs) concentrations <1.2 (Group A) and those with Crs > or =1.2 mg/dL not requiring hemodialysis (Group B). The outcomes of the procedure for these 2 groups were compared. Different variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…16,18,19 ; (6) can EVAR be done safely in patients with pre-existing renal impairment? 11,[31][32][33][34] ; and (7) does baseline renal insufficiency increase perioperative and long-term morbidity and mortality? 8 Nearly all published studies of the effect of EVAR on renal function are limited by short follow-up, lack of open control groups, variable definitions of postoperative renal dysfunction, use of serum creatinine level (SCr) instead of creatinine clearance (CrCl) or glomerular filtration rates (GFR) as a measure of renal function, and a multitude of other confounding variables.…”
mentioning
confidence: 99%
“…16,18,19 ; (6) can EVAR be done safely in patients with pre-existing renal impairment? 11,[31][32][33][34] ; and (7) does baseline renal insufficiency increase perioperative and long-term morbidity and mortality? 8 Nearly all published studies of the effect of EVAR on renal function are limited by short follow-up, lack of open control groups, variable definitions of postoperative renal dysfunction, use of serum creatinine level (SCr) instead of creatinine clearance (CrCl) or glomerular filtration rates (GFR) as a measure of renal function, and a multitude of other confounding variables.…”
mentioning
confidence: 99%
“…The methodological quality of each study is shown in Table 2. Of the 31 studies, 13 collected data prospectively 11,12,[15][16][17][18][19][20][21][22][23] whereas 18 used retrospective data from health records. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Two studies used variables such as age, sex, cardiovascular risk factors, and surgical risk, to match patients with normal kidney function to those with chronic kidney disease.…”
mentioning
confidence: 99%
“…26 General complication rates were also found to be higher in patients with preoperative renal insufficiency (30.1%) versus patients with normal preoperative renal function (18.6%). 32 A high creatinine level appeared to be an important risk factor for mortality in our study of patients. The underlying pathologic mechanism is, however, not completely understood.…”
Section: Laboratory Test Predictors Of Prognosis After Evarmentioning
confidence: 50%
“…Whereas our meta-analysis demonstrated that serum creatinine levels correlate relatively well to perioperative mortality in mostly elective repair, studies of ruptured AAA showed less consistent results. [29][30][31][32] Anain and colleagues showed that preoperative creatinine using a cutoff value of 1.5 mg/dL was associated with increased risk of 30-day mortality, although this was not significant. 31 Acosta and colleagues and Sharif and colleagues found that preoperative creatinine using a cutoff of 2.15 mg/dL was no significant predictor of in-hospital mortality.…”
Section: Creatininementioning
confidence: 99%